(3NWI GdYed dEfWdGbI fGLMI (B:s (3GdJMOjGJ(B- (3GdHfGA(B- (3GdJchjf(B- (3GdJbOje (B/s - (3ahHQ adjO, ChOhs; (3ZGRj, CMeO CfjSs ((3GdQjGV(B: s (3ecJHI GdYHjcGf(B, s, 2005)
(3GdJNWjW aj GdYed gh GdNWhI GdChdi fMh GdfLGM(B- (3echfGJ NWI GdYed(B- (3GdeDSSI(B( (3GdeTQhY(B)- (3GdEOGQI hGdYfGUQ GdYGedI NWhGJ JWhjQ GdeDSSI(B- (3GdShb hMGdI GdefGaSI(B- (3GdaQU hGdeLGRaGJ(B.s
Keywords: (3EOGQI GdCYeGds; (3GdEOGQIs; (3GdYeds